The swallowed man - Carey, Edward, 1970- (Riverhead Books, 2020)
"In the small Tuscan town of Collodi, a lonely woodcarver longs for the companionship of a son. One day, "as if the wood commanded me," Giuseppe--better known as Geppetto--carves for himself a pinewood boy, a marionette he hopes to take on tour worldwide. But when his handsome new creation comes magically to life, the woodcarver screams at him . . . and the boy, Pinocchio, leaps from his arms and escapes into the night. Though he returns the next day, the wily boy torments his father, challenging his authority and making up stories--whereupon his nose, the very nose his father carved, grows before his eyes like an antler. When the boy disappears after one last fight, the father follows a rumor to the coast and out into the sea, where he is swallowed by a great fish--and consumed by guilt, as he hunkers in the creature's belly awaiting the day when he will reconcile with the son he drove away. With all the charm, atmosphere, and emotional depth for which Edward Carey is known--and featuring his trademark fantastical illustrations--The Swallowed Man is a parable of parenthood, loss, and letting go, from a creative mind on a par with Gregory Maguire, Neil Gaiman, and Tim Burton"--